Prediction of Inefficiency in Health Insurance Administration Institutions in Indonesia using Light Gradient Boosting Machine - Kevin Valerian Ninia; Binti Sholihah; Abdul Rochman (Penerbitan Universitas Trisakti, 2023)
Everyone understands that health is something that must be considered and should not be ignored. Therefore, the government seeks to form institutions that can organize health social security for the community. However, in practice it is not often found that there are cases of waste in the services provided (inefficiency). So that research was carried out using the Light Gradient Boosting Machine (LightGBM) to provide solutions for solving cases of waste (inefficiency) in health social security administering institutions.